Perwujudan nilai sosial dan pelestarian budaya dalam ritual bersih desa Tlogomas Malang: tinjauan antropolinguistik - Wulan, Diah Ayu (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This study aims to examine the Karuman tradition procession, lexical and cultural meanings in the supporting elements of the village clean tradition, and elements that have cultural meanings to support the creation of values in the Karuman tradition through an anthropolinguistic approach. This ritual functions as a form of community gratitude for welfare, safety, and respect for ancestors. The research used a qualitative method with a descriptive approach, where data were collected through interviews and direct observation of the ritual procession. Data analysis followed the Miles & Huberman model, which includes data reduction, presentation, and conclusion drawing. The results showed that the clean village ritual contains various symbols and cultural values expressed through language, actions, and traditional symbols. For example, elements of offerings such as incense, frankincense, and traditional food have a literal meaning and deep cultural meaning in the spiritual and social life of the Tlogomas community. Anthropolinguistic studies highlight how language and symbols in this ritual function to maintain the sustainability of local culture amid the influence of modernity. The findings confirm that the clean village ritual in Tlogomas serves as a means of cultural preservation and strengthens social values such as mutual cooperation, helping, and kinship.